Asymptomatic optic nerve lesions: An underestimated cause of silent retinal atrophy in MS. (9th June 2020) - Davion, Jean-Baptiste; Lopes, Renaud; Drumez, Élodie; Labreuche, Julien; Hadhoum, Nawal; Lannoy, Julien; Vermersch, Patrick; Pruvo, Jean-Pierre; Leclerc, Xavier; Zéphir, Hélène; Outteryck, Olivier
Abstract : Objective: To evaluate the frequency of asymptomatic optic nerve lesions and their role in the asymptomatic retinal neuroaxonal loss observed in multiple sclerosis (MS). Methods: We included patients with remitting-relapsing MS in the VWIMS study (Analysis of Neurodegenerative Process Within Visual Ways In Multiple Sclerosis) (ClinicalTrials.gov Identifier: 03656055). Included patients underwent optical coherence tomography (OCT), optic nerve and brain MRI, and low-contrast visual acuity measurement. In eyes of patients with MS without optic neuritis (MS-NON), an optic nerve lesion on MRI (3D double inversion recovery [DIR] sequence) was considered as an asymptomatic lesion. We considered the following OCT/MRI measures: peripapillary retinal nerve fiber layer thickness, macular ganglion cell + inner plexiform layer (mGCIPL) volumes, optic nerve lesion length, T2 lesion burden, and fractional anisotropy within optic radiations. Results: An optic nerve lesion was detected in half of MS-NON eyes. Compared to optic nerves without any lesion and independently of the optic radiation lesions, the asymptomatic lesions were associated with thinner inner retinal layers ( p < 0.0001) and a lower contrast visual acuity ( p ⩽ 0.003). Within eyes with asymptomatic optic nerve lesions, optic nerve lesion length was the only MRI measure significantly associated with retinal neuroaxonal loss ( p < 0.03). Intereye mGCIPL thickness difference (IETD) was lower in patients with bilateral optic nerve DIR hypersignal compared to patients with unilateral hypersignal ( p = 0.0317). For the diagnosis of history of optic neuritis, sensitivity of 3D DIR and of mGCIPL IETD were 84.9% and 63.5%, respectively. Conclusions: Asymptomatic optic nerve lesions are an underestimated and preponderant cause of retinal neuroaxonal loss in MS. 3D DIR sequence may be more sensitive than IETD measured by OCT for the detection of optic nerve lesions.